Pengaruh Coworker Support terhadap Turnover Intention Melalui Organizational Embeddedness pada PT. BCA KCP Kapas Krampung Surabaya - Ngestreini, Rahmadani Nadya; Budiono, Budiono (Jurnal Ilmu Manajemen, 2021)
Working in the financial services sector, such as assurance and banking, can be stressful for employees. However, employees who have organizational attachments and coworkers support will reduce turnover. This investigation intends to analyze the impact of coworker support on turnover intention through organizational embeddedness as an intermediary variable at PT. BCA KCP Kapas Krampung Surabaya. The sampling technique used saturated samples with a total of 34 employees. Data were gathered by conducting interviews and spreading questionnaires to employees, then processed using SmartPLS 3.3.3 software tools. The finding proves that coworker support has a significantly positive effect either on organizational embeddedness and turnover intention. Furthermore, organizational embeddedness also holds a significant and negative influence on turnover intention. This result supported the existing theories based on a thorough analysis of the literature.